﻿Drug therapy monitoring (TDM) of Digoxin: safety and efficacy review - Rony Abdi Syahputra; Urip Harahap; Aminah Dalimunthe; M. Pandapotan Nasution; Denny Satria (Pensoft Publishers, 2022)
Digoxin was developed as a novel medication for the treatment of heart failure and atrial fibrillation (AF) 200 years ago. This investigation began with a PubMed and Google Scholar search for various papers using the terms digoxin safety and efficacy, digoxin in heart failure, and digoxin in atrial fibrillation. Digoxin should be administered at a dose of 0.5-0.7 ng/mL in individuals with heart failure and reduced ejection fraction. Digoxin should be administered to decrease hospital readmissions, although SDC, creatinine, and potassium levels should be continuously maintained to limit the risk of toxicity. Digoxin may be used in conjunction with diuretics, spironolactone, ACE inhibitors, or beta-blockers. It is preferable to take digoxin on a regular basis. Digoxin should not be used in the pre-excitation syndrome because it can result in the rapid development of accessory route conductors, which can finally result in ventricular fibrillation. Due to the narrow therapeutic index of digoxin, it requires appropriate treatment and continuous monitoring.